Recensão Crítica do livro “Domestic Violence: Interdisciplinary Perspectives on Protection, Prevention and Intervention” - Saraiva, Pedro (Revista de Ciências Sociais, 2019)
Resenha de Hilder, Sarah; Bettinson, Vanessa (eds.), (2016), Domestic Violence: Interdisciplinary Perspectives on Protection, Prevention and Intervention. Londres: Palgrave Macmillan.